The effect of heat processing on triterpene glycosides and antioxidant activity of herbal pegaga (Centella asiatica l. Urban) drink - Kormin, Saniah (2005)
The health benefit of herbal pegaga drink, which is associated with triterpene glycosides content and antioxidant activity attract a lot of interest from the public and food and herbal industries. The works carried in this research investigated the effect of heat processing at 65 C/15 minutes, 80 C/5minutes and pasteurization at 80 C/5minutes followed by canning and boiling at 100 C/10 minutes on these phytochemicals and compared to untreated herbal pegaga drink or fresh sample. The results revealed that the untreated pegaga drink exhibited much higher (P<0.05) antioxidant activity than the heat-treated samples. The Ferric Reducing Ability of Plasm (FRAP) values was 860 Âµmol/litre for the untreated sample and in the range of 404 - 740 Âµmol/litre for heattreated sample. The untreated drink inhibited about 72% of linoleic acid peroxidation and the percentage inhibition of heat-treated samples were in the ranged of 26-56%. The FRAP and Ferric Thiocyanate (FTC) assays were strongly correlated (r=0.93) towards the assessment of antioxidant activity in pegaga drink samples. The concentration of ascorbic acid and total polyphenol after heat treatment were 0.7 mg/100ml to 1.76 mg/100ml and 730.27 mg/100ml to 903.23 mg/100ml, respectively. Phenolic compound was found as the major contributor to the antioxidant activity in pegaga drink. Analysis of the triterpene glycosides content was performed using an isocratic High Peformance Liquid Chromatography system (HPLC). Heat processing resulted in a several fold decreased of total triterpene glycosides. The amount in untreated drink was 10.8 to 17.3% higher than those in heat-treated pegaga drinks. The present study indicated that the herbal pegaga drinks samples still retain appreciable amount of madecassoside, madecassic acid, asiaticoside, asiatic acid and polyphenol compounds. These phytochemicals are good sources of antioxidant.